The rebellion by employing the vernacular slang - Al-Zahra, Majdaa Abd; Saleh, Farah Ghanem (Al-Adab Journal, 2022)
The poet (Mowafak Muhammad) is distinguished by breaking the ordinary and his means to that by his creative poetic stamp, so he transcends his language to creativity and difference by charging it with the common vernacular language. Because he does not want his text to be elitist only, but rather he wants simple people to share their suffering and troubles and their daily lives, so we find that he includes various types of compositions, such as a song, a song, a song from the heritage, etc., or the colloquial vocabulary in his poem.